Not Just a Phase: Queer Girlhood and Coming of Age on Screen. Issue 1 (1st March 2019) - Monaghan, Whitney
Abstract : In this article, I seek to interrogate the visibility of queer girls in contemporary cinema. I demonstrate how queerness has long been associated with a passing phase of adolescent development in the teen media sphere. I reflect on the nuanced relationships between queerness and girlhood in four contemporary US independent queer films, arguing that Pariah (2011), Mosquita y Mari (2012), First Girl I Loved (2016), and Princess Cyd (2017) are representative of a new wave of queer girlhood on screen. Rejecting the pervasive tropes of coming out as coming of age and just a phase, these films use queer girlhood to challenge linear models of girlhood.